Peningkatan Mutu Pendidikan Politik Perempuan Bali Menuju Terwujudnya Kesetaraan Gender - I Gede Sudiarta (UHN IGB Sugriwa Denpasar, 2019)
General description of women's participation in the political world in Indonesia representation is very low at all levels of decision making, both at the executive, legislative and judicial levels in the government bureaucracy, political parties both in other public societies. In this case the low quality of women's participation in politics occurs in Bali, namely in the executive ranks. Likewise, at the echelon II level, there were no women who obtained the position, that is, from the number of village heads in Bali there were no women who held more positions as lurah, even if there were only a few. In addition, in the organization of the Lembaga Pemberdayaan Masyarakat (LPM) in Bali, it is rare and there may not be women who become the Bendesa Adat or Bendesa Pakraman. This is also evident in the management of other organizations such as youth clubs and sekuna teruna. In an organization like this it is rare to find women becoming chairpersons or electing a chairperson as chairman or vice chairman. Based on this, a gender perspective is considered by involving men and women in the basic decision-making process of democratic work that will lead to equality.